Malaysian Sustainable Housing: The Study of Traditional Terengganu Architecture on Spatial Characteristics in Terrapuri Heritage Village Towards The Development of Sustainable Spatial Layout in Malaysian Home - Sabil, Azmal (International Journal of Sustainable Construction Engineering and Technology, 2025)
Terengganu's architectural identity has developed through long-standing cultural and commercial exchanges with regions such as Siam, Cambodia, and Indonesia. These ties have contributed to a notable architectural tradition, ranked as an early expression of Malay civilisation. However, this architectural tradition has been affected by rapid globalization, as modern and contemporary design have significantly neglected the identity of traditional architectural values. Contemporary interpretations of modern housing are often seen as lacking authenticity and failing to reflect the region's traditional character. This study aimed to identify and investigate the distinctive spatial characteristics of traditional Terengganu architecture, focusing on their role in defining the region's cultural identity along the east coast of Peninsular Malaysia. The research employed a qualitative approach involving document review, interviews with a resort owner, and field observations. Three traditional buildings at Terrapuri Heritage Village in Setiu were selected as case studies, supported by detailed spatial mapping. The findings indicate that, while the original spatial design of the houses remains intact, they have undergone several transformations over time. These include modifying traditional space usage, such as converting the kitchen into a bathing area and reconstructing aging structural components using modern materials and construction techniques. These forms of adaptation demonstrate how traditional spatial arrangements can remain functional in contemporary contexts. The study highlighted the relevance of Terengganu's traditional spatial characteristics in the contemporary design context, indicating that its principles offer valuable insights for the development of future Malaysian housing models that integrate sustainability aspects with cultural integrity.